Find answers, ask questions, and connect with our
community around the world.

Activity Discussion Math Simplify: 4z + 5(z – 3) – 2z

  • Simplify: 4z + 5(z – 3) – 2z

    Posted by Emeli on July 8, 2024 at 10:11 am

    Simplify: 4z + 5(z – 3) – 2z

    brajesh replied 3 days, 14 hours ago 2 Members · 1 Reply
  • 1 Reply
  • brajesh

    Member
    July 12, 2024 at 12:37 pm
    Helpful
    Up
    0
    Down
    Not Helpful
    ::

    To simplify the expression <math xmlns=”http://www.w3.org/1998/Math/MathML”><semantics><mrow><mn>4</mn><mi>z</mi><mo>+</mo><mn>5</mn><mo stretchy=”false”>(</mo><mi>z</mi><mo>−</mo><mn>3</mn><mo stretchy=”false”>)</mo><mo>−</mo><mn>2</mn><mi>z</mi></mrow><annotation encoding=”application/x-tex”>4z + 5(z – 3) – 2z</annotation></semantics></math>4z+5(z−3)−2z, follow these steps:

    1. Distribute the <math xmlns=”http://www.w3.org/1998/Math/MathML”><semantics><mrow><mn>5</mn></mrow><annotation encoding=”application/x-tex”>5</annotation></semantics></math>5 across the terms inside the parentheses:

      <math xmlns=”http://www.w3.org/1998/Math/MathML” display=”block”><semantics><mrow><mn>4</mn><mi>z</mi><mo>+</mo><mn>5</mn><mo stretchy=”false”>(</mo><mi>z</mi><mo>−</mo><mn>3</mn><mo stretchy=”false”>)</mo><mo>−</mo><mn>2</mn><mi>z</mi><mo>=</mo><mn>4</mn><mi>z</mi><mo>+</mo><mn>5</mn><mi>z</mi><mo>−</mo><mn>15</mn><mo>−</mo><mn>2</mn><mi>z</mi></mrow><annotation encoding=”application/x-tex”>4z + 5(z – 3) – 2z = 4z + 5z – 15 – 2z</annotation></semantics></math>4z+5(z−3)−2z=4z+5z−15−2z

    2. Combine the like terms:

      <math xmlns=”http://www.w3.org/1998/Math/MathML” display=”block”><semantics><mrow><mo stretchy=”false”>(</mo><mn>4</mn><mi>z</mi><mo>+</mo><mn>5</mn><mi>z</mi><mo>−</mo><mn>2</mn><mi>z</mi><mo stretchy=”false”>)</mo><mo>−</mo><mn>15</mn></mrow><annotation encoding=”application/x-tex”>(4z + 5z – 2z) – 15</annotation></semantics></math>(4z+5z−2z)−15

      Add the <math xmlns=”http://www.w3.org/1998/Math/MathML”><semantics><mrow><mi>z</mi></mrow><annotation encoding=”application/x-tex”>z</annotation></semantics></math>z terms together:

      <math xmlns=”http://www.w3.org/1998/Math/MathML” display=”block”><semantics><mrow><mn>4</mn><mi>z</mi><mo>+</mo><mn>5</mn><mi>z</mi><mo>−</mo><mn>2</mn><mi>z</mi><mo>=</mo><mn>7</mn><mi>z</mi></mrow><annotation encoding=”application/x-tex”>4z + 5z – 2z = 7z</annotation></semantics></math>4z+5z−2z=7z

    3. Finally, write the simplified expression:

      <math xmlns=”http://www.w3.org/1998/Math/MathML” display=”block”><semantics><mrow><mn>7</mn><mi>z</mi><mo>−</mo><mn>15</mn></mrow><annotation encoding=”application/x-tex”>7z – 15</annotation></semantics></math>7z−15

    So, the simplified form of the expression is <math xmlns=”http://www.w3.org/1998/Math/MathML”><semantics><mrow><mn>7</mn><mi>z</mi><mo>−</mo><mn>15</mn></mrow><annotation encoding=”application/x-tex”>7z – 15</annotation></semantics></math>7z−15.

For Worksheets & PrintablesJoin Now
+